Role of Sildenafil in Management of Pediatric Acute Respiratory Distress Syndrome - Janagill, Monika; Pooni, Puneet Aulakh; Bhargava, Siddharth; Chhabra, Shibba Takkar (Journal of Pediatric Intensive Care, 2021)
Acute respiratory distress syndrome (ARDS) has high mortality and multiple therapeutic strategies have been used to improve the outcome. Inhaled nitric oxide (INO), a pulmonary vasodilator, is used to improve oxygenation. This study was conducted to determine the role of sildenafil, an oral vasodilator, to improve oxygenation and mortality in pediatric ARDS (PARDS). The prevalence of pulmonary hypertension in PARDS was studied as well. Inclusion criteria included children (1–18 years) with ARDS requiring invasive ventilation admitted to the pediatric intensive care unit of a teaching hospital in Northern India over a 1-year period of time. Thirty-five patients met the inclusion criteria. Pulmonary arterial pressure (PAP) was determined by echocardiogram. Patients with persistent hypoxemia were started on oral sildenafil. The majority of patients (77%) had a primary pulmonary etiology of PARDS. Elevated PAP (>25 mm Hg) was detected in 54.3% patients at admission. Sildenafil was given to 20 patients who had severe and persistent hypoxemia. Oxygenation improved in most patients after the first dose with statistically significant improvement in PaO2/FiO2 ratios at both 12 and 24 hours following initiation of therapeutic dosing of sildenafil. Improvement in oxygenation occurred irrespective of initial PAP. Outcomes included a total of 57.1% patients discharged, 28.6% discharged against medical advice (DAMA), and a 14.3% mortality rate. Mortality was related to the severity of PARDS and not the use of sildenafil. This is the first study to determine the effect of sildenafil in PARDS. Sildenafil led to improvement in oxygenation in nearly all the cases without affecting mortality. Due to unavailability of INO in most centers of developing countries, sildenafil may be considered as an inexpensive alternative in cases of persistent hypoxemia in PARDS. We recommend additional randomized controlled trials to confirm the effect of sildenafil in PARDS as determined in this study.
Keywords: ARDS; oxygenation; pulmonary arterial hypertension; sildenafil